2020
DOI: 10.17240/aibuefd.2020.20.58249-632620
|View full text |Cite
|
Sign up to set email alerts
|

Üni̇versi̇te Öğrenci̇leri̇ni̇n Uzaktan Öğrenme Ortamlarina İli̇şki̇n Görüşleri̇ İle İngi̇li̇zce Ders Başarisi Arasindaki̇ İli̇şki̇ni̇n Görünümü

Abstract: Üniversite öğrencilerinin uzaktan eğitim öğrenme ortamlarına ilişkin görüşleri ve İngilizce ders başarısı arasındaki ilişkinin incelendiği ve ilişkisel tarama modelinde yürütülen bu çalışmaya toplam 924 lisans ve ön lisans öğrencisi katılmıştır. Araştırmada, Kişisel Bilgi Formu, Web-Tabanlı Öğrenme Ölçeği ve İngilizce II dersi başarı notları kullanılmıştır. Öğrencilerin, öğretmen desteği, öğrenci iletişim ve iş birliği, kişisel ilgi, otantik (gerçekçi) öğrenme, aktif öğrenme, öğrenci özerkliği ve memnuniyet ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…However, in another study conducted before COVID-19 pandemics, Srichanyachon (2013) concluded that students' attitudes towards online learning environments were moderate. Although published in 2020, in another study conducted in the pre-COVID-19 period, Karakış (2020) found that students had positive opinions about all the dimensions of distance education learning environments including teacher support, student communication and collaboration, personal relevance, authentic (realistic) learning, active learning, student autonomy and satisfaction. This information from the literature suggest that it is possible to claim that students' views on distance education learning environments have decreased from medium or above medium level in the pre-pandemic period to below medium levels in the current COVID-19 pandemic period, during which students are made to receive education through distance education learning environments compulsorily.…”
Section: Student Opinions About Distance Education Learning Environmentsmentioning
confidence: 99%
“…However, in another study conducted before COVID-19 pandemics, Srichanyachon (2013) concluded that students' attitudes towards online learning environments were moderate. Although published in 2020, in another study conducted in the pre-COVID-19 period, Karakış (2020) found that students had positive opinions about all the dimensions of distance education learning environments including teacher support, student communication and collaboration, personal relevance, authentic (realistic) learning, active learning, student autonomy and satisfaction. This information from the literature suggest that it is possible to claim that students' views on distance education learning environments have decreased from medium or above medium level in the pre-pandemic period to below medium levels in the current COVID-19 pandemic period, during which students are made to receive education through distance education learning environments compulsorily.…”
Section: Student Opinions About Distance Education Learning Environmentsmentioning
confidence: 99%